Liver transplantation for haemophiliacs with hepatitis C cirrhosis. Issue 6 (December 1996) - McCarthy, M; Gane, E; Pereira, S; Tibbs, C J; Heaton, N; Rela, M; Hambley, H; Williams, R
Abstract : BACKGROUND: Experience of liver transplantation in haemophiliacs with end stage hepatitis C liver disease is limited and particularly difficult questions are raised when there is also HIV infection. AIMS: This is the first report in Great Britain to describe the operative replacement therapy and initial outcome in four haemophiliacs with end stage HCV cirrhosis. PATIENTS: Two patients had factor VIII, one had factor IX, and one had factor X deficiency. One patient had also contracted HIV infection from factor replacement but had no AIDS defining illnesses. METHODS: Intraoperatively patients were given either factor VIII infusions, factor IX bolus, or fresh frozen plasma, according to formulae devised to calculate exact clotting factor requirements. Baseline preoperative coagulation studies included prothrombin time, activated partial thromboplastin time, fibrinogen concentrations, and factor VIII, IX, and X concentrations. Factor concentrations were then assayed at 12, 24, 48, and 72 hours postoperatively. RESULTS: Postoperatively all patients had coagulation factor concentrations sustained within the normal ranges by 72 hours unsupported (137, 125, 95, 104 IU/dl), representing de novo synthesis by the graft. Transfusion requirements during the operative and immediate post-transplant period were no greater than those of patients without clotting disorders. Two patients had episodes of bleeding postoperatively, one of which was fatal, occurring at the site of a previous untreated subdural bleed. In both instances the bleeding occurred in the presence of normal concentrations of clotting factor. The remaining three patients are at 6, 6, and 12 months post-transplant and remarkably improved clinically with sustained factor concentrations. One patient has evidence of graft dysfunction from HCV recurrence and all have evidence of recurrent viraemia with HCV on polymerase chain reaction studies. CONCLUSIONS: Orthotopic liver transplantation should be considered in haemophiliac patients with end stage liver disease from hepatitis C infection with or without concomitant HIV infection. Their clinical condition is likely to be greatly improved by orthotopic liver transplantation and the haemophilia cured with only a small risk of severe graft dysfunction from recurrent HCV infection.